Examining muscle synergy composition and segmental coordination during overground walking in individuals with a rotationplasty about the knee - Kellen T. Krajewski; Nathan Rogers; Mia A. Lundin; Andrea Rogers; Susan Kanai; Lucas Moore; Steven W. Thorpe; James J. Carollo; Patrick M. Carry; David R. Howell; Lauren A. Sepp; Anne K. Silverman; et al. (Scientific Reports)
Abstract Rotationplasty is a surgical technique used to salvage the limb following resection of a sarcoma or to address congenital defects. The procedure repurposes the ankle as a new knee, while fusing the thigh and shank musculature to achieve ‘knee’ flexion/extension. Most unique is the retainment of original innervations of the distal and proximal musculature, thus requiring spinal reorganization to coordinate the separate muscles as a single tensile unit. Lower body kinematics, intersegmental coordination, and electromyography (EMG) derived muscle synergies of nine participants are quantified during overground walking. Half the sample exhibited ‘normal’ ‘knee’ kinematics with fused muscles exhibiting synced temporal dynamics of EMG activity in the surgical limb. The congruent EMG activity between fused muscles, especially the gastrocnemius with the rectus femoris, suggests successful spinal reorganization to achieve cooperative contraction as a single tensile unit. Conversely, a few individuals were categorized as ‘low’ knee function categorized by low dynamic peak range of the knee joint which may be explained by the observed discordant EMG activity between the fused muscles. The most substantial characteristic differences between the ‘high’ and ‘low’ knee functioning individuals were age and time since surgery, with the ‘low’ being younger and having a shorter time since surgery.